English for Children: Teaching Material Model for Students of Primary School Teacher Education - Dayu Retno Puspita; Asih Rosnaningsih (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
To improve the quality of English learning in English courses for children, students need learning resources that can improve language skills in accordance with the characteristics and needs of students as prospective English teacher in Primary School. The research aims to develop a model of teaching materials for the English for Children course in accordance with the needs of students in the Primary School Teacher Education Study Program. The research was designed using an R&D development model. This research used test subjects by carrying out validity tests on teaching materials experts, material experts, the responses of ten students in small group trials and twenty-five students in large group trials. Data was collected using a questionnaire instrument and analyzed descriptively, quantitatively and qualitatively. The research shows that the teaching material products from chapters 1 to chapter 8 are sequentially: 1) English theoretical concepts related to teaching children; 2) the concept of developing an English learning plan for children; 3) the concept of children's characteristics in learning English; 4) the concept of teaching four English skills (listening, speaking, reading, writing); 5) the concept of teaching through songs; 6) the concept of teaching through stories; 7) the concept of teaching through games;  and 8) the concept of technology-assisted teaching. The results of the validator of teaching material experts, material experts and the results of student responses in small and large group trials are categorized as very valid so that English for Children teaching materials are suitable for use.